Implementasi Nilai Aswaja Pada Mata Pelajaran Ke-NU-an di SMK Ma’arif 5 Gombong Kebumen - Chasanah, Maryam Anisatun; Najitama, Fikria; Kusumaningratri, Rose (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
The purpose of this study is to analyze the values of aswaja in the fikhiyah rules on the NU subjects at SMK Ma'arif 5 Gombong, the implementation of aswaja values in NU-an subjects at SMK Ma'arif 5 Gombong, as well as population and inhibiting factors along with evaluation of the implementation of Aswaja values at SMK Ma'arif 5 Gombong. This research is in the form of field research and the methods used in this study are interview methods, observation methods, and documentation methods. The data was collected based on interviews with the head of SMK Ma'arif 5 Gombong, NU-an teacher and class XII students of SMK Ma'arif 5 Gombong. Based on the results of the study, the implementation of the Aswaja value in the NU subject at SMK Ma'arif 5 Gombong is as follows: (1) the Aswaja value related to the rules of fikhiyah Nahdlatul Ulama includes; rule al muhafadzah 'ala al qadimi as sholih wa al akdzu bi al jadidi al – ahslah, rule al 'adah muhakkamah ma lam tukhali al-syara', and the rule of ma la yudraku kulluhu la yutraku kulluh; (2) the implementation of the Aswaja Value in nu jurisprudence rules takes place through learning planning, learning processes, and evaluation; and(3) factors that support and hinder the implementation of aswaja values related to NU's fikhiyah rules are caused by intrinsic factors and extrinsic factors. The main supporting factor is the existence of pesantren An Nahdliyah 5 so that the application of Aswaja values in schools follows. The obstacles include; students come from different schools and presumption that the subject of nu-ness is less important